AB0583 Long-Term Integrated Treatment with Bosentan and Iloprost Increases, Independently from Other Clinical Characteristics, The Absolute Number of Capillaries in Systemic Sclerosis Patients: A Nailfold Capillaroscopic Analysis. (15th July 2016) - Trombetta, A.C.; Sulli, A.; Pizzorni, C.; Paolino, S.; Alessandri, E.; Smith, V.; Ruaro, B.; Cutolo, M.
Abstract : Background: Iloprost (ILO) and bosentan (BOSE) integrated therapy was demonstrated to improve microvascular structure in systemic sclerosis (SSc) patients, in two long-term follow up studies [1]. Objectives: Since the alterations in capillary number seem to predict the incidence of clinical SSc complications [2], present study aimed to quantify, by nailfold videocapillaroscopy (NVC), long-term effects of BOSE treatment on nailfold capillary absolute number and their possible correlation with clinical parameters of the disease. Methods: Thirty SSc patients entered the study, with a follow up of for 4 years. Fifteen patients were treated with ILO mono-therapy (80 μg/day, for 5 continuous days, every 3 months), while other 15 patients, because of the onset of systolic pulmonary hypertension (sPAP) or digital ulcers (DUs) were treated with BOSE (125 mg twice/day) and ILO integrated therapy (ILO+BOSE). Nailfold capillaries absolute number, DU incidence, diffusing capacity of the lung for carbon monoxide (DLCO), sPAP and renal artery resistive index (RI) were evaluated yearly. Friedman test, Cochran's q test, Marginal homogeneity and mixed modelling were used to study variables with repeated measures. A p value lower then 0.05 was considered significant. Results: In the ILO+BOSE group, capillary absolute number was found to have a significant increase (p=0.01) from T0: 6.8±1.3 to T4: 7.8±1.5 (14.7%), whereas in the ILO group, a non-significant decrease in capillary number from T0: 7.18±0.5 to T4: 6.5±1.1 (9.4%) was found. According to multivariate analysis, the most significant associations, other then BOSE treatment, were observed between capillary number increase and baseline capillaroscopic "Early" pattern (p<0.0001), lcSSc subtype (p=0.001), while it was independent from other clinical characteristics. In the ILO+BOSE group there was a significant reduction in the annual incidence of new DUs from T0 (10/15 patients) to T4 (2/15 patients) (80%; p=0.0042) and no further negative significant changes were observed in DLCO and sPAP. On the contrary, in the ILO group, DLCO was significantly reduced (8.1%, p=0.039) and sPAP increased (15%, p=0.04) during the follow up. RI did not change significantly in both groups. Conclusions: Capillary absolute number count seems a reliable parameter to evaluate long-term effects of BOSE on microvasculature in SSc. A significant reduction in the annual incidence of new DUs and stabilization of lung function was observed and appeared to be associated to the increased number of capillaries during a four-years integrated treatment with BOSE and ILO. References: Cutolo M et al. 2013;40:40–5. Smith V et al. 2011;70:180–3. Disclosure of Interest: None declared